The rate and role of diaphragmatic peritonectomy in optimal cytoreduction in patients with advanced stage ovarian cancer: a prospective study of 100 patients - Lūža, Tomas; Ožalinskaitė, Agnė; Rudaitis, Vilius (Acta medica Lituanica, 2014)
Background. Diaphragmatic peritoneal metastasis by advanced epithelial ovarian cancer is a very common holdback precluding optimal cytoreduction. The aim of this study was to determine the rate of diaphragmatic peritonectomy during optimal cytoreductive surgery and its role in postoperative morbidity and survival in patients with advanced ovarian cancer. Materials and methods. 100 consecutive patients with advanced epithelial ovarian cancer underwent cytoreductive surgery and were followed up prospectively (January 2009 – March 2014). Characteristics of surgery, rate of diaphragmatic peritonectomy and post operative complications were assessed. The Kaplan-Meier method was used for survival analysis. Results. The median age of the entire cohort at the time of primary cytoreduction was 58.5 years (23–83). Optimal cytoreduction was achieved in 73 cases out of 100 patients. From 73 patients in 30 cases (41.1%) upper abdominal procedures, specifically diaphragmatic peritonectomy, was performed to achieve the main goal of cytoreduction – no visible or palbable disease at the end of cytoreduction. Non-optimal cytoreduction was achieved in 27 cases. According to the Clavien-Dindo complication grading system grade I and grade II complications occurred more often in patients that underwent diaphragmatic surgery. The median overall survival from the time of diagnosis to the last follow-up or death was 28 months (range 0–63 months). The factors associated with the longest survival after primary cytoreductive surgery were the disease free interval from the primary cytoreduction of more than 19 months (n = 51) versus less than 19 months (n = 49) (95% confidence interval, 51.7–59.5; P = 0.013) and no visible or palpable residual disease at the end of cytoreduction (n = 73) versus visible or palpable residual disease (n = 27) (95% confidence interval, 52.7–61.2; P = 0.03). Conclusions. Based on our prospective analysis of advanced ovarian cancer patients, diaphragmatic peritonectomy is feasible and safe, ensures better rates of optimal cytoreduction and should not be an obstacle towards better survival.